Imbalance between the function of Na+-K+-2Cl and K+-Cl impairs Cl– homeostasis in human focal cortical dysplasia - Liu, Ru; Xing, Yue; Zhang, Herui; Wang, Junling; Lai, Huanling; Cheng, Lipeng; Li, Donghong; Yu, Tao; Yan, Xiaoming; Xu, Cuiping; Piao, Yueshan; Zeng, Linghui; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective Altered expression patterns of Na+-K+-2Cl– (NKCC1) and K+-Cl– (KCC2) co-transporters have been implicated in the pathogenesis of epilepsy. Here, we assessed the effects of imbalanced NKCC1 and KCC2 on γ-aminobutyric acidergic (GABAergic) neurotransmission in certain brain regions involved in human focal cortical dysplasia (FCD). Materials and methods We sought to map a micro-macro neuronal network to better understand the epileptogenesis mechanism. In patients with FCD, we resected cortical tissue from the seizure the onset zone (SOZ) and the non-seizure onset zone (non-SOZ) inside the epileptogenic zone (EZ). Additionally, we resected non-epileptic neocortical tissue from the patients with mesial temporal lobe epilepsy (MTLE) as control. All of tissues were analyzed using perforated patch recordings. NKCC1 and KCC2 co-transporters expression and distribution were analyzed by immunohistochemistry and western blotting. Results Results revealed that depolarized GABAergic signals were observed in pyramidal neurons in the SOZ and non-SOZ groups compared with the control group. The total number of pyramidal neurons showing GABAergic spontaneous postsynaptic currents was 11/14, 7/17, and 0/12 in the SOZ, non-SOZ, and control groups, respectively. The depolarizing GABAergic response was significantly dampened by the specific NKCC1 inhibitor bumetanide (BUM). Patients with FCD exhibited higher expression and internalized distribution of KCC2, particularly in the SOZ group. Conclusion Our results provide evidence of a potential neurocircuit underpinning SOZ epileptogenesis and non-SOZ seizure susceptibility. Imbalanced function of NKCC1 and KCC2 may affect chloride ion homeostasis in neurons and alter GABAergic inhibitory action, thereby contributing to epileptogenesis in FCDs. Maintaining chloride ion homeostasis in the neurons may represent a new avenue for the development of novel anti-seizure medications (ASMs).